Identification of deep water lantern sharks (Chondrichthyes : Etmopteridae) using morphometric data and multivariate analysis - Coelho, R. (2016)
Taxonomic distinction to species level of deep water sharks is complex and often impossible to achieve during fisheries-related studies. The species of the genus Etmopterus are particularly difficult to identify, so they often appear without species assignation as Etmopetrus sp. or spp. in studies, even those focusing on elasmobranchs. During this work, the morphometric traits of two species of Etmopterus, E. spinax and E. pusillus were studied using 27 different morphological measurements, relatively easy to obtain even in the field. These measurements were processed with multivariate analysis in order to find out the most important ones likely to separate the two species. Sexual dimorphism was also assessed using the same techniques, and it was found that it does not occur in these species. The two Etmopterus species presented in this study share the same habitats in the overlapping ranges of distribution and are caught together on the outer shelves and slopes of the north-eastern Atlantic.